Could it be colic? Horse-owner decision making and practices in response to equine colic - Scantlebury, Claire E (BioMed Central, 2014)
BACKGROUND: Little is known about lay understanding and decision making in response to colic. Horse-owners/carers are key to identifying colic and initiating veterinary intervention. Understanding how owners think and act in relation to colic could assist veterinary surgeons in tailoring information about colic with the aim of improving colic outcomes. METHODS: A mixed methods approach was employed including qualitative in-depth interviews and a cross-sectional questionnaire. Qualitative data were analysed using Grounded theory to conceptualise processes involved in horse-owner management of colic. Following this, a cross-sectional survey was designed to test these concepts. Cluster analysis explored the role of the human-horse relationship upon colic management strategies. RESULTS: Fifteen horse-owners with a range of colic experience participated in the interviews. A theoretical conceptual model was developed and described how horse-owners’ recognised, assessed and responded to colic. Three main management strategies were used including ‘wait and see’, ‘lay treatments’ and ‘seek veterinary assistance’. Actions in response to colic were moderated by owners’ experience of colic and interpretation of the severity of colic signs. A postal questionnaire gathered data from 673 horse-owners from the North-West of the UK. The majority (605, 89.9%) of respondents were female. Cluster analysis revealed 5 meaningful groups of horse-owners based upon assessment of questionnaire items on the human-horse relationship. These groups included 2 professional and 3 amateur owner typologies. There were differences in the responses to some questionnaire items among the identified groups. CONCLUSIONS: This study describes lay understanding and management of colic among a population of horse-owners from the North-West of the UK. The information may serve as a basis upon which to tailor existing programmes designed to educate owners about colic management strategies, and may inform veterinarians’ interactions with horse-owners.